Progressive supranuclear palsy phenotype mimicking synucleinopathies - Menšíková, Kateřina; Matěj, Radoslav; Tučková, Lucie; Rusina, Robert; Ehrmann, Jiří; Kaňovský, Petr (Journal of the neurological sciences, 2013)
BACKGROUND: Atypical parkinsonian syndromes are currently divided into two groups based on their pathological appearance: synucleinopathies and tauopathies. Based on recent clinico-pathological studies it is increasingly clear, that some pathological characteristics are shared by both groups. STUDY OBJECTIVE: To describe two pathologically proven cases of tauopathy manifesting in vivo in two typical synucleinopathy phenotypes: multiple system atrophy and dementia with Lewy bodies. PATIENTS AND METHODS: There were 67-year-old woman with a phenotype of multiple system atrophy and a 70-year-old man with a phenotype of dementia with Lewy bodies. The clinical diagnosis was based on the commonly used clinical diagnostic criteria. A detailed neuropathological examination of the brain was conducted post-mortem in both cases. RESULTS: The overall pathological picture corresponded with a rare combination of two neurodegenerative entities: 4R tauopathy (meeting the diagnostic criteria for typical progressive supranuclear palsy) and neocortical stage of Alzheimer's disease. CONCLUSION: The interesting feature in both our cases was the presence of dual pathology: diffuse tauopathy and Alzheimer's pathology. We believe, that our two unique cases should serve as an evidence that tauopathies such as CBS and PSP might mimic practically anything from the family of atypical parkinsonian syndromes, particularly when another concomitant neurodegenerative disease is present.
Keywords: senioři; mozková amyloidní angiopatie; Multiple System Atrophy; demence s Lewyho tělísky; lidé; Supranuclear Palsy, Progressive; mužské pohlaví; fenotyp; synukleiny; progresivní supranukleární obrna; amyloidní beta-protein; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Phenotype; ženské pohlaví; Humans; Synucleins; multisystémová atrofie; Lewy Body Disease; Amyloid beta-Peptides; Female; Aged; Cerebral Amyloid Angiopathy; Male